Avoiding delay in diagnosing melanoma of the foot. Issue 3 (March 2018) - Murphy, Bryan; Dolan, Olivia
Cutaneous melanoma is a relatively rare, but potentially aggressive, cancer. Although more commonly seen in the elderly, a rise among younger patients has been observed. Melanoma arising on the foot or within nail units is unusual. It can often go unnoticed or mistaken for benign conditions, with definitive diagnosis occurring at an advanced stage; therefore, requiring more complex surgery and leading to a worse prognosis. All healthcare professionals managing foot conditions have an important role in early detection. Greater awareness of the signs and symptoms of melanoma and referral pathways will ensure timely assessment and earlier intervention.